Controllable pitch propeller control with fast backpropagation algorithm - Alarcin, Fuat; Ekinci, Serkan; Gulez, Kayhan (SOC NAVAL ARCHITECTS & MARINE ENGINEERS, 2007)
In this paper, controllable pitch propeller (CPP) has been used to improve the maneuvering at a fixed shaft speed. The proportional-derivative (PD) control method has been applied to obtain high efficiency by changing the pitch angle. The controller results have been evaluated and learned by a fast backpropagation algorithm (FBA). The neural network results show that learning of pitch behavior has been verified, and the FBA performance of CPP controller is better than that of the PD controller.
Keywords: Engineering; Oceanography